Rebuilding Social Democracy : Core Principles for the Centre Left - Hickson, Kevin, 1974- (Book collections on Project MUSE., 2016)
Reclaiming Social Democracy is the first major reappraisal of social democracy on the centre-left since election of Jeremy Corbyn. With a foreword by Lord Hain, it examines its foundational principles and identifies the values needed to find a route back to political credibility for Labour.